Monocarboxylate Transporter 8 Deficiency: Delayed or Permanent Hypomyelination? - Vancamp, Pieter; Demeneix, Barbara A.; Remaud, Sylvie (Frontiers in Endocrinology, 2020)
Monocarboxylate transporter 8 (MCT8) deficiency or the Allan-Herndon-Dudley Syndrome (AHDS) is an X-linked psychomotor disability syndrome with around 320 clinical cases described worldwide. SLC16A2 gene mutations, encoding the thyroid hormone (TH) transporter MCT8, result in intellectual disability due to impaired TH uptake in the developing brain. MCT8 deficiency is a multi-organ affecting disease with a predominant neuronal cell-based pathology, with the glial component inadequately investigated. However, deficiency in myelin, a key component of white matter (WM) enabling fast nerve conduction, is a TH-dependent hallmark of the disease. Nevertheless, analysis of the myelin status in AHDS patients has led to conflicting interpretations. The majority of individual case studies reported delayed myelination, that was restored later in life. In contrast, post-mortem studies and high-resolution MRIs detected WM (micro-)abnormalities throughout adolescence, suggesting permanent hypomyelination. Thus, interpretations vary depending on methodology to investigate WM microstructure. Further, it is unknown whether the mutation within the MCT8 is linked to the severity of the myelin deficiency. Consequently, terminology is inconsistent among reports, and AHDS is occasionally misdiagnosed as another WM disorder. The evolutionary conserved TH signalling pathway that promotes the generation of myelinating oligodendrocytes enabled deciphering how the lack of MCT8 might affect myelinogenesis. Linking patient findings on myelination to those obtained from models of MCT8 deficiency revealed underlying pathophysiological mechanisms, but knowledge gaps remain, notably how myelination progresses both spatially and temporally in MCT8 deficiency. This limits predicting how myelin integrity might benefit therapeutically, and when to initiate. A recurrent observation in clinical trials is the absence of neurological improvement. Testing MCT8-independent thyromimetics in models, and evaluating treatments used in other demyelinating diseases, despite different aetiologies, is crucial to propose new therapeutic strategies combatting this devastating disease.